1868 Fla. Laws 2538, Persons Engaged in Criminal Offence, Having Weapons, ch. 7, § 10 - (:unkn) unknown (General Publisher, 1868)
Prohibited the carrying of a slungshot, metallic knuckles, billies, firearms or other dangerous weapon if arrested for committing a criminal offence or disturbance of the peace. Punishable by imprisonment up to 3 months or a fine up to $100.
--
Keywords: CARRY - INTENT TO COMMIT CRIME